Impact of digital tools on the research writing process: A case study of collaborative writing in computer science. (August 2018) - Hynninen, Niina
Highlights: Different digital tools were used for different purposes along a text trajectory. Real-time collaborative writing tools were adapted for writer needs. Twitter was used to advertise and share work but also to find resources. Findings highlight the importance of social media in post-publication activities. Abstract: This paper reports on a case study on collaborative research writing in computer science, with particular focus on the researchers' use of digital writing and social media tools. The research paper is still a prominent genre in the field, but technological advances such as the development of real-time collaborative writing tools and social media have created new opportunities for collaboration as well as the sharing of research results. This paper takes a closer look at how digital tools, particularly collaborative writing tools and Twitter, are utilised in the process of producing a research paper for publication, and how the authors and their colleagues view the role of such tools in the text production process. The data include a text history of a research paper, as well as research interviews with the main authors and their colleagues. The data have been approached from a local practices perspective, considering the paper as part of the writing practices of the multicultural research group where the authors worked. The interviews provide further perspectives on the researchers' use of digital tools. The findings shed light on collaborative research writing practices, particularly how collaborative writing tools, which enable new practices such as synchronous writing, may not be utilised by the researchers in the ways intended by the developers. The findings also highlight the significance of social media tools, particularly Twitter, in post-publication activities, with important implications for researcher education.